Bipolar solid-state battery and its preparation process and electronic device
By using heat sealing tape in bipolar solid-state batteries for thermal isostatic pressure treatment, the thermosetting layer is formed, which solves the problems of cumbersome packaging and poor circulation performance in the prior art, and achieves efficient packaging and stability improvement.
Patent Information
- Application Number
- CN202411346405.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing bipolar solid-state batteries have cumbersome packaging methods, resulting in poor packaging effect and poor circulation performance.
A heat sealing tape containing a prepolymer layer and a support layer is used to surround the solid electrolyte layer, and the prepolymer layer undergoes cross-linking and polymerization reaction to form a thermoset layer through thermal isostatic pressure treatment, thereby achieving the bonding of the bipolar sheet.
The packaging process is simplified, the packaging strength and stability are improved, and the circulation performance of bipolar solid-state batteries is significantly improved.
Smart Images

Figure CN118888863B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bipolar solid-state battery and a preparation process and electronic equipment thereof. Background Art
[0002] Bipolar battery technology is the use of internal series connection inside the battery, which can greatly increase the output voltage and output power of the battery. In the prior art, bipolar batteries generally have bipolar liquid batteries and bipolar solid-state batteries. When preparing a bipolar liquid battery, it is necessary to inject electrolyte between the edges of two bipolar sheets separated by a diaphragm and set insulation and seals for packaging. In order to avoid battery liquid short circuit and cause battery failure, the insulation and seal materials at the edges of the bipolar sheets, as well as the sealing method are very important. Although bipolar solid-state batteries do not have the problem of electrolyte flow and can avoid the occurrence of liquid short circuit, the current packaging methods all use light curing or hot pressing curing methods, which either require special materials and repeated sealing several times to obtain the required sealing effect. The manufacturing process is very cumbersome and time-consuming, labor-intensive and costly, or the packaging effect is not good, and the resulting battery has poor cycle performance. German patent application DE102018204522A1 discloses a bipolar battery preparation process using UV sealing materials for sealing. In this process, photocuring must be performed once each unit is assembled (i.e., a sealant layer is formed between two adjacent bipolar sheets) to ensure sufficient exposure to ultraviolet rays. The required sealing effect can only be achieved through several photocuring processes. Photocuring also needs to consider multiple factors such as the irradiation path, and the packaging process is cumbersome. Summary of the invention
[0003] In order to solve the problem that the packaging process in the preparation process of bipolar solid-state batteries in the prior art is complicated, the packaging effect is not good, and the cycle performance of the obtained bipolar solid-state battery is poor, the present invention provides a bipolar solid-state battery and its preparation process and electronic equipment. The preparation process of the bipolar solid-state battery of the present invention is simple to operate, and only one-step hot isostatic pressing treatment is required for the entire laminate to achieve an excellent packaging effect, thereby improving the cycle performance of the obtained bipolar solid-state battery.
[0004] To achieve the above objectives, the present invention adopts the following technical solutions.
[0005] In a first aspect, the present invention provides a process for preparing a bipolar solid-state battery, which comprises the following steps:
[0006] S1. Provide a stack: the stack comprises at least two stacked bipolar sheets; the bipolar sheets comprise a positive electrode active material layer and a negative electrode active material layer respectively arranged on two surfaces of a bipolar current collector; a solid electrolyte layer and a heat-sealing tape are arranged between two adjacent bipolar sheets, the heat-sealing tape surrounds the solid electrolyte layer, and the solid electrolyte layer is respectively in contact with the positive electrode active material layer and the negative electrode active material layer of the two adjacent bipolar sheets; wherein the heat-sealing tape comprises at least two stacked prepolymer layers and at least one supporting layer, the prepolymer layer is in contact with two adjacent bipolar sheets, and the prepolymer layer comprises a prepolymer, an initiator and a cross-linking agent;
[0007] S2. subjecting the laminate to hot isostatic pressing, wherein the prepolymerized layer undergoes a cross-linking polymerization reaction to form a thermosetting layer to achieve encapsulation.
[0008] In a second aspect, the present invention provides a bipolar solid-state battery, which is prepared using the bipolar solid-state battery preparation process described above.
[0009] In a third aspect, the present invention provides an electronic device comprising the bipolar solid-state battery as described above.
[0010] The positive and progressive effects of the present invention are:
[0011] The present invention provides a preparation process for a bipolar solid-state battery, wherein a heat-sealing tape comprising a prepolymer layer and a supporting layer is provided between two adjacent bipolar sheets, so that the heat-sealing tape surrounds the solid electrolyte layer, and after all the multiple layers or all the bipolar sheets are stacked to obtain a laminate, the laminate is simply subjected to a one-step hot isostatic pressing treatment as a whole, thereby achieving the packaging of the bipolar solid-state battery, and having an excellent packaging effect. During the hot isostatic pressing treatment, the prepolymer undergoes a cross-linking polymerization reaction under the action of an initiator and a cross-linking agent, and the prepolymer layer forms a thermosetting layer in situ, thereby achieving full bonding to the bipolar sheet. On the one hand, such a packaging method is fast and efficient; on the other hand, the bonding method of the heat-sealing tape forming a thermosetting layer in situ through a cross-linking polymerization reaction has strong bonding properties, and its bonding performance to the bipolar sheet is significantly improved, which can improve the packaging strength and stability of the bipolar solid-state battery, thereby improving the cycle performance of the resulting bipolar solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Schematic diagram of the structure of the laminate obtained in Example 1.
[0013] Reference numerals:
[0014] Pre-polymer layer 1
[0015] Support layer 2
[0016] Heat sealing tape 3
[0017] Bipolar Plate 4
[0018] Positive electrode active material layer 5
[0019] Negative electrode active material layer 6
[0020] Bipolar current collector 7
[0021] Solid electrolyte layer 8 DETAILED DESCRIPTION
[0022] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0023] Preparation process of bipolar solid-state battery
[0024] In the preparation process of the bipolar solid-state battery provided in the first aspect of the present invention, it comprises the following steps:
[0025] S1. Provide a stack: the stack comprises at least two stacked bipolar sheets; the bipolar sheets comprise a positive electrode active material layer and a negative electrode active material layer respectively arranged on two surfaces of a bipolar current collector; a solid electrolyte layer and a heat-sealing tape are arranged between two adjacent bipolar sheets, the heat-sealing tape surrounds the solid electrolyte layer, and the solid electrolyte layer is respectively in contact with the positive electrode active material layer and the negative electrode active material layer of the two adjacent bipolar sheets; wherein the heat-sealing tape comprises at least two stacked prepolymer layers and at least one supporting layer, the prepolymer layer is in contact with two adjacent bipolar sheets, and the prepolymer layer comprises a prepolymer, an initiator and a cross-linking agent;
[0026] S2. subjecting the laminate to hot isostatic pressing, wherein the prepolymerized layer undergoes a cross-linking polymerization reaction to form a thermosetting layer to achieve encapsulation.
[0027] In some optional embodiments, the temperature of the hot isostatic pressing treatment is 90-140°C.
[0028] In some optional embodiments, the hot isostatic pressing treatment time is 5-20 minutes, such as 10 minutes.
[0029] In a preferred embodiment, in the heat-sealing tape, the stacking is alternating stacking.
[0030] In a preferred embodiment, the heat-sealing tape comprises two prepolymer layers and a support layer, wherein the support layer is disposed between the two prepolymer layers.
[0031] In the present invention, the prepolymer may be a thermoplastic polymer. The thermoplastic polymer may be a conventional polymer in the art that can be polymerized to form a thermosetting polymer after heating.
[0032] In some preferred embodiments, the thermoplastic polymer is a thermoplastic polymer containing CH bonds.
[0033] In some more preferred embodiments, the prepolymer is a thermoplastic polymer, and the thermoplastic polymer includes one or more of ethylene-vinyl acetate copolymer (EVA), polyolefin thermoplastic elastomer (POE), polyacrylate and derivatives thereof.
[0034] In some alternative embodiments, the initiator comprises a peroxide.
[0035] In some preferred embodiments, the initiator is a peroxide, and the peroxide includes one or both of tert-butyl peroxy-2-ethylhexyl carbonate (TBEC) and 1,4-bis-tert-butylperoxyisopropylbenzene (BIPB).
[0036] In some optional embodiments, the crosslinking agent includes a silane coupling agent.
[0037] In some preferred embodiments, the crosslinking agent is a silane coupling agent, which includes one or more of vinyl silane coupling agents, chloroalkyl silane coupling agents, aminoalkyl silane coupling agents, epoxyalkyl silane coupling agents, sulfur-containing hydrocarbon silane coupling agents, pseudohalogen silane coupling agents and quaternary aminoalkyl silane coupling agents; for example, one or more of vinyl trichloroalkyl, chloropropyl trichlorosilane, aminopropyl triethoxysilane, (2,3-epoxypropyloxy)propyl trimethoxysilane, mercaptopropyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane (KH-570).
[0038] In some optional embodiments, the support layer includes one or more of polyethylene terephthalate (PET), polyimide (PI) and polytetrafluoroethylene (PTFE).
[0039] In some optional embodiments, the content of the initiator is 0.1%-0.2%, where the percentage is the mass percentage of the initiator to the mass percentage of the prepolymer.
[0040] In some optional embodiments, the content of the cross-linking agent is 1%-2%, where the percentage is the mass percentage of the cross-linking agent to the mass percentage of the prepolymer.
[0041] In the present invention, the initiator and cross-linking agent and their dosage need to be adjusted according to the prepolymer and the applicable scenario (such as temperature) to achieve the best effect. The mechanism of the polymerization reaction is common knowledge in the art and will not be repeated here.
[0042] In some optional embodiments, the prepolymer layer has a thickness of 10-50 microns, such as 20 microns.
[0043] In some optional embodiments, the support layer has a thickness of 100-180 microns, such as 150 microns.
[0044] In some optional embodiments, the thickness ratio of the prepolymer layer to the support layer is 1:(2.5-25).
[0045] In the present invention, the heat-sealing tape can be prepared by co-extruding the raw materials of the support layer and the prepolymer layer, wherein the co-extrusion is preferably cast co-extrusion.
[0046] In some embodiments, the solid electrolyte layer includes a solid electrolyte and a binder, wherein the solid electrolyte is, for example, Li6PS5Cl, and the binder is, for example, polytetrafluoroethylene; and the mass ratio of the solid electrolyte to the binder is, for example, 99:1.
[0047] In some embodiments, the thickness of the solid electrolyte layer is, for example, 50 μm.
[0048] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductor, a positive electrode binder and a first solid electrolyte; the negative electrode active material layer includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a second solid electrolyte.
[0049] In a specific embodiment, the mass ratio of the positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the first solid electrolyte is 75:1:1:23.
[0050] In a specific embodiment, the mass ratio of the negative electrode active material, the negative electrode binder, the negative electrode conductive agent and the second solid electrolyte is 75:1:1:23.
[0051] In some embodiments, the bipolar current collector is a stacked structure, wherein one layer is a positive electrode metal sheet and the other layer is a negative electrode metal sheet.
[0052] In a specific embodiment, the bipolar current collector is a laminated structure, wherein one layer is aluminum foil and the other layer is copper foil, wherein the aluminum foil is used as the positive electrode metal sheet and the copper foil is used as the negative electrode metal sheet.
[0053] In some embodiments, the first solid electrolyte and the second solid electrolyte may be electrolyte materials conventionally used in lithium-ion batteries in the art, for example, each independently being one or more of sulfides, halides, oxides, and polymers. The sulfide is, for example, Li6PS5Cl (LPSC); the halide is, for example, Li3InCl6 (LIC); the oxide is, for example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (LATP); the polymer is, for example, polyethylene oxide / lithium bis(trifluoromethylsulfonyl)imide (PEO / LiTFSI).
[0054] In some optional embodiments, the positive electrode active material includes one or more of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium-rich manganese-based oxide (LRMO) and lithium-containing phosphate. Among them, the lithium-containing phosphate includes but is not limited to lithium iron manganese phosphate, lithium iron phosphate (LFP) and lithium manganese phosphate.
[0055] In some optional embodiments, the positive electrode binder is selected from one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0056] In some optional embodiments, the positive electrode conductive agent is selected from one or more of carbon black, acetylene black, graphene, carbon nanotubes and carbon nanofibers.
[0057] In some optional embodiments, the negative electrode active material is selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, pure silicon, silicon oxide compounds and silicon carbon compounds.
[0058] In some optional embodiments, the negative electrode conductive agent is selected from one or more of carbon black (Super P), acetylene black, graphene, carbon nanotubes and carbon nanofibers.
[0059] In some optional embodiments, the negative electrode binder is selected from one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), lithium polyacrylate (PAALi), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA) and styrene-butadiene rubber (SBR).
[0060] In some embodiments, the method for preparing the bipolar sheet comprises the following steps:
[0061] The positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the first solid electrolyte are dispersed in a first non-polar solvent to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the surface of the positive electrode metal sheet of the bipolar current collector, and after drying and cold pressing, a positive electrode active material layer is formed on the positive electrode metal sheet; the negative electrode active material, the negative electrode binder, the negative electrode conductive agent and the second solid electrolyte are dispersed in a second non-polar solvent to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the surface of the negative electrode metal sheet of the bipolar current collector, and after drying and cold pressing, a negative electrode active material layer is formed on the negative electrode metal sheet, so as to obtain a bipolar sheet.
[0062] In some embodiments, the first non-polar solvent and the second non-polar solvent are non-polar solvents conventionally used in the art, for example, each independently is one or more of xylene, butyl butyrate, anisole, isobutyl isobutyrate and toluene.
[0063] In a specific embodiment, the first non-polar solvent and the second non-polar solvent are both xylene.
[0064] Bipolar solid-state battery
[0065] In the bipolar solid-state battery provided in the second aspect of the present invention, it is prepared using the bipolar solid-state battery preparation process as described above.
[0066] Electronic devices
[0067] In the electronic device provided in the third aspect of the present invention, it includes the bipolar solid-state battery as described above.
[0068] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0069] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention. The present invention is further illustrated by way of examples below, but the present invention is not limited to the scope of the embodiments described. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications. Unless otherwise specified, the reagents and raw materials used in the present invention are commercially available.
[0070] The main reagents and raw materials used in the following examples and comparative examples are as follows:
[0071] Ethylene-vinyl acetate copolymer (EVA) was purchased from Jinan Jinbang Environmental Protection Technology Co., Ltd., model VAE;
[0072] The polyolefin thermoplastic elastomer material (POE) was purchased from Dow Chemical, model number ENGAGE™ 11000 POE;
[0073] Tert-butyl peroxy-2-ethylhexyl carbonate (TBEC) was purchased from Aladdin, model number T303370;
[0074] 1,4-Di-tert-butylperoxyisopropylbenzene (BIPB) was purchased from Jinan Guochen Taifu Chemical Co., Ltd., model BIPB;
[0075] γ-Methacryloxypropyltrimethoxysilane (KH-570) was purchased from Leyan, model number 1228708;
[0076] Vinyltrichlorosilane was purchased from McLean, model number T830195;
[0077] Polyethylene terephthalate (PET) was purchased from McLean, model number P875573;
[0078] Polyimide (PI) was purchased from MacLean, model number P874997;
[0079] Polytetrafluoroethylene (PTFE) was purchased from McLean, model number 767293;
[0080] Lithium iron phosphate (LFP) was purchased from Aladdin, model number L302983;
[0081] Conductive carbon black (Super P) was purchased from Shenzhen Kejing, model SUPER C65;
[0082] Polyvinylidene fluoride (PVDF) was purchased from Shenzhen Kejing, model HSV900;
[0083] Li6PS5Cl was purchased from Shenzhen Kejing, model number is LPSCl.
[0084] Example 1
[0085] The specific preparation process of the bipolar solid-state battery in this embodiment is as follows:
[0086] (1) Preparation of heat-sealing tape 3:
[0087] ① Add peroxide TBEC and silane coupling agent KH-570 to the prepolymer EVA and mix them evenly to obtain a mixture, wherein the mass of peroxide TBEC accounts for 0.1% of the mass of EVA, and the mass of silane coupling agent KH-570 accounts for 1% of the mass of EVA;
[0088] ② The mixed material is added into a single screw extruder and co-extruded with the PET casting forming the support layer 2 to obtain a heat-sealing tape 3; the heat-sealing tape 3 is a three-layer structure, with the upper and lower surface layers being prepolymer layers 1 and the middle being a support layer 2, the thickness of the two prepolymer layers 1 being 20 μm, and the thickness of the support layer 2 being 150 μm.
[0089] (2) Preparation of bipolar sheet 4: LFP, Super P, PVDF and Li6PS5Cl are dispersed in xylene at a mass ratio of 75:1:1:23 to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the surface of the aluminum foil of the bipolar current collector 7. After drying and cold pressing, a positive electrode active material layer 5 is formed on the aluminum foil. Then, graphite, Super P, PVDF and Li6PS5Cl are dispersed in xylene at a mass ratio of 75:1:1:23 to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the surface of the copper foil of the bipolar current collector 7. After drying and cold pressing, a negative electrode active material layer 6 is formed on the copper foil, and a bipolar sheet 4 having a positive electrode active material layer 5 and a negative electrode active material layer 6 respectively disposed on both surfaces of the bipolar current collector 7 can be obtained.
[0090] (3) Preparation of solid electrolyte layer 8: Li6PS5Cl and PTFE were fully mixed at a mass ratio of 99:1 to fully fiberize the PTFE, and then rolled repeatedly to a thickness of 50 μm.
[0091] (4) Preparation process of bipolar solid-state battery:
[0092] Step S1, providing a laminate:
[0093] ① A solid electrolyte layer 8 is stacked on the positive electrode active material layer 5 of the first bipolar sheet 4, a heat-sealing tape 3 is arranged around the solid electrolyte layer 8, and then a second bipolar sheet 4 is stacked so that the negative electrode active material layer 6 of the bipolar sheet 4 is in contact with the solid electrolyte layer 8. In this way, the heat-sealing tape 3 is filled between the two bipolar sheets 4, and the upper and lower surface prepolymer layers 1 of the heat-sealing tape 3 along the stacking direction are respectively attached to the first bipolar sheet 4 and the second bipolar sheet 4;
[0094] ② Continue to stack the solid electrolyte layer 8 on the positive active material layer 5 of the second bipolar sheet 4, set the heat sealing tape 3 around the solid electrolyte layer 8, and then stack the third bipolar sheet 4 so that the negative active material layer 6 of the bipolar sheet 4 is in contact with the solid electrolyte layer 8, and so on, stack a total of 13 bipolar sheets 4 to obtain a stacked body.
[0095] Step S2: subjecting the laminate to hot isostatic pressing:
[0096] The temperature of the hot isostatic pressing treatment is 120° C., and the time of the hot isostatic pressing treatment is 10 minutes. During this process, the prepolymer layer 1 in the heat-sealing tape 3 undergoes a cross-linking reaction, and a thermosetting layer is formed in situ, achieving full bonding of two adjacent bipolar sheets 4, thereby completing the packaging of the stack and obtaining a bipolar solid-state battery.
[0097] In step S1, the structural schematic diagram of the obtained laminate is as follows Figure 1 As shown. In the stack, the bipolar sheet 4 includes a bipolar current collector 7, a positive electrode active material layer 5 is arranged on the aluminum foil of the bipolar current collector 7, and a negative electrode active material layer 6 is arranged on the copper foil of the bipolar current collector 7; a solid electrolyte layer 8 and a heat-sealing tape 3 are arranged between two adjacent bipolar sheets 4, the heat-sealing tape 3 surrounds the solid electrolyte layer 8, and the solid electrolyte layer 8 is in contact with the positive electrode active material layer 5 and the negative electrode active material layer 6 of the two adjacent bipolar sheets 4 respectively; wherein the heat-sealing tape 3 includes two prepolymer layers 1 and one support layer 2, and the prepolymer layer 1 is in contact with the two adjacent bipolar sheets 4; the thickness of the prepolymer layer 1 is 20 μm, and the thickness of the support layer 2 is 150 μm; the thickness of the solid electrolyte layer 8 is 50 μm.
[0098] It should be noted that the number of bipolar sheets and solid electrolyte layers in a bipolar solid-state battery can be set according to actual needs. In addition, along the stacking direction of the bipolar sheets and the solid electrolyte layers, the electrode sheet at the top layer can be a bipolar sheet or a electrode sheet including only a positive electrode active material layer or a negative electrode active material layer. The above scheme is a conventional setting process of a bipolar solid-state battery and will not be repeated here.
[0099] Example 2
[0100] The difference between this embodiment and embodiment 1 is that the prepolymer EVA in the heat-sealing tape is replaced with POE, and the other conditions are the same as those in embodiment 1.
[0101] Example 3
[0102] The difference between this embodiment and embodiment 1 is that the initiator TBEC in the heat-sealing tape is replaced with BIPB, and the other conditions are the same as those in embodiment 1.
[0103] Example 4
[0104] The difference between this embodiment and embodiment 1 is that the supporting layer PET in the heat-sealing tape is replaced with PI, and the other conditions are the same as those in embodiment 1.
[0105] Example 5
[0106] The only difference between this embodiment and embodiment 1 is that the temperature of the hot isostatic pressing treatment in the preparation process of the bipolar solid-state battery is 90° C., and the other conditions remain the same as in embodiment 1.
[0107] Example 6
[0108] The only difference between this embodiment and embodiment 1 is that the temperature of the hot isostatic pressing treatment in the preparation process of the bipolar solid-state battery is 140° C., and the other conditions remain the same as in embodiment 1.
[0109] Example 7
[0110] The difference between this embodiment and embodiment 1 is that the content of the initiator TBEC in the heat-sealing tape is 0.20%, and the other conditions are the same as those in embodiment 1.
[0111] Example 8
[0112] The difference between this embodiment and embodiment 1 is that the content of the initiator TBEC in the heat-sealing tape is 0.15%, and the other conditions are the same as those in embodiment 1.
[0113] Example 9
[0114] The only difference between this embodiment and embodiment 1 is that the content of the cross-linking agent KH-570 in the heat-sealing tape is 2%, and the other conditions are the same as those in embodiment 1.
[0115] Example 10
[0116] The difference between this embodiment and embodiment 1 is that the content of the cross-linking agent KH-570 in the heat-sealing tape is 1.5%, and the other conditions are the same as those in embodiment 1.
[0117] Embodiment 11
[0118] The difference between this embodiment and embodiment 1 is that the cross-linking agent KH-570 in the heat-sealing tape is replaced with vinyl trichlorosilane, and the other conditions are the same as those in embodiment 1.
[0119] Example 12
[0120] The difference between this embodiment and embodiment 1 is that the thickness of the prepolymer layer in the heat-sealing tape is 10 μm, and the other conditions are the same as those in embodiment 1.
[0121] Example 13
[0122] The difference between this embodiment and embodiment 1 is that the thickness of the prepolymer layer in the heat-sealing tape is 180 μm, and the other conditions are the same as those in embodiment 1.
[0123] Comparative Example 1
[0124] The difference between this comparative example and Example 1 is that the prepolymer EVA in the heat-sealing tape is replaced with PTFE (which cannot be post-crosslinked and has no stickiness), and the other conditions are the same as those in Example 1.
[0125] Comparative Example 2
[0126] The difference between this comparative example and Example 1 is that the heat-sealing tape does not contain peroxide TBEC, and the other conditions are the same as those in Example 1.
[0127] Comparative Example 3
[0128] The difference between this comparative example and Example 1 is that the heat-sealing tape does not contain the cross-linking agent KH-570, and the other conditions are the same as those in Example 1.
[0129] Comparative Example 4
[0130] The difference between this comparative example and Example 1 is that the heat-sealing tape does not contain the supporting layer PET, and the other conditions are the same as those in Example 1.
[0131] Comparative Example 5
[0132] The difference between this comparative example and Example 1 is that the prepolymer layer of the heat-sealing tape contains only prepolymer EVA, and does not contain TBEC and KH-570. The other conditions are the same as those in Example 1.
[0133] The specific conditions and parameters in the above Examples 1-13 and Comparative Examples 1-5 are shown in Table 1.
[0134] Application Example 1
[0135] A mobile phone comprises a control device, an output device and a power source, wherein the control device is a chip, the output device is a screen, and the power source is the bipolar solid-state battery in Examples 1-13.
[0136] Application Example 2
[0137] A pure electric vehicle comprises an engine and a power source, wherein the power source adopts the bipolar solid-state battery in Examples 1-13.
[0138] Application Example 3
[0139] An electric train comprises an engine and a power source, wherein the power source adopts the bipolar solid-state battery in Examples 1-13.
[0140] Effect Example 1
[0141] The bipolar sheets prepared in Examples 1-13 and Comparative Examples 1-5 were used to test the peeling force between the thermosetting layer and the bipolar sheet. The specific test steps are as follows:
[0142] Take the bipolar sheets prepared in Examples 1-13 and Comparative Examples 1-5, and use a die cutter to cut bipolar sheets with a length × width of 400mm × 20mm. Take a flat thin steel plate with a length of 200-300mm and a width of 40mm. First, stick a double-sided tape (length of 150mm, width of 20mm) on the center of the steel plate, smooth it with force, and ensure that the double-sided tape is tightly attached to the center of the steel plate. Peel off the double-sided tape to get the adhesive strip, attach the bipolar sheet to the adhesive strip, ensure that the bipolar sheet and the adhesive strip are completely attached, and fix the steel plate on the lower clamp of the universal material testing machine and fix it vertically; insert the other bipolar sheet that is not attached to the adhesive strip into the upper clamp and fix it, so that the bipolar sheet attached to the adhesive strip on the lower clamp is 180° with the bipolar sheet fixed by the upper clamp. The peeling speed is 50-100mm / min, and the test is carried out using a universal material testing machine (Instron 5940).
[0143] Effect Example 2
[0144] The bipolar solid-state batteries (lithium-ion batteries) prepared in Examples 1-13 and Comparative Examples 1-5 were tested for the number of cycles at 25° C. (the cycle capacity retention rate was 80%, i.e., 80% SOH). The specific test steps are as follows:
[0145] At 25°C, first charge and discharge the battery for one cycle at 0.1C to activate it, then connect the lithium-ion battery prepared above to the Blue Electric charge and discharge tester, and then cycle it for a long time at a rate of 0.3C until the ratio of the capacity of the nth cycle to the capacity of the first cycle at 0.3C is less than 80%, and the capacity retention rate of the n-1th cycle is defined as 80%, and the number of cycles is recorded as n-1, and the test is stopped. The operating voltage range of the battery test is 2.8V (discharge cut-off voltage) ~ 4.0V (charge cut-off voltage).
[0146] The above test results are shown in Table 1.
[0147]
[0148] Note: “ / ” in Table 1 means that the condition parameter is not involved in the specific experiment.
[0149] In the preparation process of the bipolar solid-state battery of the present invention, a heat-sealing tape is used as a sealing material. After all the bipolar sheets are stacked to obtain a laminate, the laminate only needs to be subjected to a one-step hot isostatic pressing treatment as a whole to achieve the packaging of the bipolar solid-state battery, and the packaging effect is excellent, efficient and fast. Among them, the bonding method of the thermosetting layer obtained by the in-situ cross-linking reaction of the prepolymer layer during the hot isostatic pressing process has good bonding performance, which can improve the packaging strength and stability of the bipolar solid-state battery, thereby significantly improving the cycle performance of the obtained bipolar solid-state battery. Specifically, the peeling force between the obtained thermosetting layer and the bipolar sheet in Examples 1-13 can reach more than 100N, and the number of cycles of the obtained bipolar solid-state battery at 25°C (capacity retention rate is 80%) can reach more than 3,000 cycles, or even more than 5,000 cycles.
[0150] Compared with Example 1, when the prepolymer EVA is replaced with conventional PTFE in Comparative Example 1, even after hot isostatic pressing, the bonding performance is still significantly poor, and the number of cycles of the resulting bipolar solid-state battery at 25°C is greatly reduced. This may be because PTFE cannot be cross-linked, and a thermosetting layer cannot be formed after hot isostatic pressing, and the bonding performance is poor, and the bipolar solid-state battery cannot be effectively encapsulated. Similarly, in Comparative Example 5, when only prepolymer EVA is used without a reaction aid, even after hot isostatic pressing, the bonding performance is still significantly poor, and the number of cycles of the resulting bipolar solid-state battery at 25°C is greatly reduced.
[0151] Compared with Example 1, when no peroxide (Comparative Example 2) or silane coupling agent (Comparative Example 3) is used in the prepolymer layer, after hot isostatic pressing treatment, the peeling force between the obtained thermosetting layer and the bipolar sheet is greatly reduced, and the number of cycles of the obtained bipolar solid-state battery at 25°C is significantly deteriorated.
[0152] When the heat-sealing tape in Comparative Example 4 does not contain a support layer, after hot isostatic pressing, the peeling force between the obtained thermosetting layer and the bipolar sheet is greatly reduced, and the number of cycles of the obtained bipolar solid-state battery at 25°C is also significantly deteriorated.
[0153] The temperature of the hot isostatic pressing treatment also has a certain influence on the cycle performance of the obtained bipolar solid-state battery. Compared with Example 1, when the temperature of the hot isostatic pressing treatment is appropriately reduced or increased (Examples 5 and 6), the cycle performance of the obtained bipolar solid-state battery is reduced to a certain extent.
[0154] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A process for preparing a bipolar solid-state battery, characterized in that: It includes the following steps: S1. Provide a stack: the stack comprises at least two stacked bipolar sheets; the bipolar sheets comprise a positive electrode active material layer and a negative electrode active material layer respectively arranged on the two surfaces of the bipolar current collector; a solid electrolyte layer and a heat-sealing tape are arranged between two adjacent bipolar sheets, the heat-sealing tape surrounds the solid electrolyte layer, and the solid electrolyte layer is respectively in contact with the positive electrode active material layer and the negative electrode active material layer of the two adjacent bipolar sheets; wherein the heat-sealing tape comprises at least two stacked prepolymer layers and at least one supporting layer, the prepolymer layer is in contact with two adjacent bipolar sheets, the prepolymer layer comprises a prepolymer, an initiator and a cross-linking agent; the prepolymer is a thermoplastic polymer, and the thermoplastic polymer comprises one or more of ethylene-vinyl acetate copolymer, polyolefin thermoplastic elastomer material, polyacrylate and its derivatives; the cross-linking agent comprises a silane coupling agent; S2. The laminate is subjected to hot isostatic pressing treatment; wherein the temperature of the hot isostatic pressing treatment is 90-140° C.; the prepolymerized layer undergoes a cross-linking polymerization reaction to form a thermosetting layer to achieve encapsulation.
2. The process for preparing a bipolar solid-state battery according to claim 1, characterized in that: The content of the initiator is 0.1%-0.2%, where the percentage is the mass percentage of the initiator to the mass percentage of the prepolymer; The content of the cross-linking agent is 1%-2%, and the percentage is the mass percentage of the cross-linking agent to the mass percentage of the prepolymer.
3. The process for preparing a bipolar solid-state battery according to claim 1, characterized in that: The initiator includes one or both of tert-butyl peroxy-2-ethylhexyl carbonate and 1,4-di-tert-butyl peroxyisopropylbenzene.
4. The process for preparing a bipolar solid-state battery according to claim 1, characterized in that: The cross-linking agent is a silane coupling agent, and the silane coupling agent includes one or more of vinyl silane coupling agents, chloroalkyl silane coupling agents, aminoalkyl silane coupling agents, epoxyalkyl silane coupling agents, sulfur-containing hydrocarbon silane coupling agents, pseudohalogen silane coupling agents and quaternary aminoalkyl silane coupling agents.
5. The process for preparing a bipolar solid-state battery according to claim 1, characterized in that: The support layer includes one or more of polyethylene terephthalate, polyimide and polytetrafluoroethylene.
6. The process for preparing a bipolar solid-state battery according to claim 1, characterized in that: The heat-sealing tape meets one or more of the following conditions ad: a. The thickness of the prepolymer layer is 10-50 microns; b. The thickness of the support layer is 100-180 microns; c. The thickness ratio of the prepolymer layer to the support layer is 1:(2.5-25); d. The stacking is alternating stacking.
7. A bipolar solid-state battery, characterized in that: It is prepared using the preparation process of a bipolar solid-state battery as described in any one of claims 1 to 6.
8. An electronic device, characterized in that: It includes the bipolar solid-state battery as claimed in claim 7.
Citation Information
Patent Citations
Method for manufacturing a stack of bipolar battery cells
DE102018204522A1
Method of manufacturing polymer-based bipolar battery via in situ polymerization
CN116826158A
Bipolar cell
CN1499664A